Dual benefits of Bacillus velezensis LJ-19: contact-dependent biocontrol of Fusarium wilt and growth promotion in cucumber - Li, Songwei; Li, Jingjing; Yuan, Minghui; Ren, Jingxia; Jiao, Yang; Zhao, Linjie; Wang, Yeyun; Yan, Zihan; Li, JinYu; Du, Jianfeng; Wang, Hongliang; Yang, Chenyu (Frontiers in Plant Science, 2025)
Cucumber is an important economic crop widely cultivated globally. Fusarium wilt, caused by Fusarium oxysporum f. sp. cucumerinum, seriously affects its yield and quality and is difficult to control. Here, we isolated a novel Bacillus velezensisstrain (LJ-19) from cucumber rhizosphere. Through assays for antibacterial activity, enzymatic activity, detection of disease resistance genes, and plant growth-promoting activity, this strain exhibited pronounced antagonistic activity against Fusarium oxysporum f. sp. cucumerinum and possessed plant growth-promoting traits. Notably, the inhibition of Fusarium oxysporum f. sp. cucumerinum mycelial growth and spore germination by LJ-19 was primarily contact-dependent, rather than mediated by diffusible antibiotics. Meanwhile, LJ-19 enhanced the activities of key defense enzymes—superoxide dismutase (SOD), peroxidase (POD), phenylalanine ammonia lyase (PAL), and polyphenol oxidase (PPO), thereby contributing to plant protection, and the transcript levels of defense-related genes, including Nonexpressor of pathogenesis-related genes 1 (NPR1), Pathogenesis-related gene 3 (PR3), Lipoxygenase 1 (LOX1), Constitutive triple response 1 (CTR1), and Phenylalanine ammonia-lyase 1 (PAL1), were up-regulated. Pot experiments demonstrated that LJ-19 treatment significant increased the stem thickness, fresh weight, leaf area, and overall biomass in cucumber. LJ-19 was also been confirmed could thrive in nitrogen-free environment and solubilize inorganic phosphorus, produce indole-3-acetic acid (IAA) and siderophores. Collectively, these findings demonstrate that Bacillus velezensis LJ-19 suppresses cucumber Fusarium wilt via direct antagonism and induction of systemic resistance. They also provide insights into the molecular mechanisms by which LJ-19 controls Fusarium Wilt and promotes cucumber growth, highlighting its potential as an effective biocontrol agent for sustainable cucumber.